Signalized Intersection Optimization Using PKJI 2023 And Webster For Emission Reduction - Novian Auruma Ramdhan; Irfan Hardiansyah; Veronica Veronica (CV. AFDIFAL MAJU BERKAH, 2026)
This research is motivated by the increasing traffic volume in Bantul Regency, which has led to a decline in the performance of signalized intersections and an increase in motor vehicle emissions. The purpose of this study is to evaluate the performance of Klangon 3-way intersection, Sedayu 4-way intersection, and Pedes 4-way intersection and to analyze the effectiveness of optimization using PKJI 2023 and the Webster method on traffic performance and emissions. This study uses a quantitative, descriptive, evaluative approach. The study population is all vehicle flows at signalized intersections, while the sample is determined by purposive sampling based on high-volume intersections during peak hours. The research instruments include a CTMC survey, intersection inventory forms, and geometric measurements. Data analysis techniques are carried out using PKJI 2023 to calculate capacity, degree of saturation, delay, and queue length, as well as the Webster method for signal time optimization, followed by emission estimation based on the LAPI-ITB model. The results showed that the Webster method significantly reduced delays and queue lengths, while the combined scenario provided the best results, with a delay reduction of up to 66.29 percent and reduced emissions due to reduced vehicle idle time. The study concluded that signal optimization and intersection geometric improvements are effective in improving traffic performance while reducing vehicle emissions.